Dificuldades inerentes da reciclagem de vidros no brasil e suas alternativas. - Bacchi, Angelo Albuquerque Martins (Universidade Federal de São Carlos, 2024)
Analyzing the history of humanity, it’s possible to observe that glass has always been present, whether in the form of tools, ornaments, vases, windows stained glass, bottles, glasses, kitchen utensils, and, in more recent times, in addition to all these ways mentioned, glass is also used in car windows, cell phone screens, photovoltaic cells, the glass fibers that make up the internet network, among others. With this wide range of uses and assuming the enormous consumption in society, recycling is necessary to minimize the impacts, reprocessing discarded materials and giving them a new use. In this context, the aim of this study is to understand how glass is recycled in Brazil, its inherent difficulties, and possible ways to solve them.
Inherent difficulties in recycling glass in Brazil and its alternatives.
Keywords: Reciclagem de vidros no Brasil; Dificuldades reciclagem de vidros; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS